Penerapan Bimbingan Kelompok Berbasis Hadist Untuk Meningkatkan Kedisiplinan Dalam Melaksanakan Shalat Berjamaah Pada Penerima Manfaat Sentra “Budi Perkasa” Palembang - Ragil Lutfiani; Kusnadi Kusnadi; Zhila Jannati (ScidacPlus, 2023)
Discipline in congregational prayer is very important so that each individual can obtain multiple rewards from Allah SWT. This research aims to determine the level of discipline in congregational prayers of beneficiaries (PM) before and after having hadith-based group guidance, as well as to determine the application of hadith-based group guidance in improving discipline in congregational prayers of beneficiaries. A qualitative approach with descriptive research methods was used by researchers in this research. 8 beneficiaries at the Palembang